2007
DOI: 10.1161/strokeaha.106.473967
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxic Reperfusion After Global Ischemia Decreases Hippocampal Energy Metabolism

Abstract: Background and Purpose-Previous reports indicate that compared with normoxia, 100% ventilatory O 2 during early reperfusion after global cerebral ischemia decreases hippocampal pyruvate dehydrogenase activity and increases neuronal death. However, current standards of care after cardiac arrest encourage the use of 100% O 2 during resuscitation and for an undefined period thereafter. Using a clinically relevant canine cardiac arrest model, in this study we tested the hypothesis that hyperoxic reperfusion decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 28 publications
2
73
1
4
Order By: Relevance
“…Hypoxia and/or ischemia may both lead to inadequate supplies of glucose and oxygen, followed by dose-dependent depletions of high-energy phosphates (2). Hyperoxic reoxygenation further impairs the oxidative energy metabolism in subregions of the brain (33). In line with these findings, our group has shown a slower decline in Krebs cycle intermediates in newborn pigs exposed to hypoxia followed by reoxygenation with 100% O 2 (34).…”
Section: Oxidative Phosphorylation and Hyperoxic Reoxygenationsupporting
confidence: 73%
“…Hypoxia and/or ischemia may both lead to inadequate supplies of glucose and oxygen, followed by dose-dependent depletions of high-energy phosphates (2). Hyperoxic reoxygenation further impairs the oxidative energy metabolism in subregions of the brain (33). In line with these findings, our group has shown a slower decline in Krebs cycle intermediates in newborn pigs exposed to hypoxia followed by reoxygenation with 100% O 2 (34).…”
Section: Oxidative Phosphorylation and Hyperoxic Reoxygenationsupporting
confidence: 73%
“…50 Although resumption of oxygen and metabolic substrate delivery at the microcirculatory level is essential, a growing body of evidence suggests that too much oxygen during the initial stages of reperfusion can exacerbate neuronal injury through production of free radicals and mitochondrial injury (see section on oxygenation). 51,52 Beyond the initial reperfusion phase, several factors can potentially compromise cerebral oxygen delivery and possibly secondary injury in the hours to days after cardiac arrest. These include hypotension, hypoxemia, impaired cerebrovascular autoregulation, and brain edema; however, human data are limited to small case series.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%
“…Although it is important to ensure that patients are not hypoxemic, a growing body of preclinical evidence suggests that hyperoxia during the early stages of reperfusion harms postischemic neurons by causing excessive oxidative stress. 51,52,143,144 Most relevant to post-cardiac arrest care, ventilation with 100% oxygen for the first hour after ROSC resulted in worse neurological outcome than immediate adjustment of the FIO 2 to produce an arterial oxygen saturation of 94% to 96%. 145 On the basis of preclinical evidence alone, unnecessary arterial hyperoxia should be avoided, especially during the initial post-cardiac arrest period.…”
Section: Oxygenationmentioning
confidence: 99%
“…A few studies reported findings similar to ours. For example, Richards et al, (2007) measured O 2 metabolism in beagles using a 13 C NMR method and found that hyperoxia treatment after ischemia reduced O 2 metabolism. Working with a rat model, Harik et al, (1995) measured glucose metabolism with a 2-deoxyglucose method and observed that hypoxia with 10% FiO 2 increased glucose metabolism by 10% to 40%.…”
Section: Physiological Considerationsmentioning
confidence: 99%